The economic dynamics of work - Haley, M. Ryan (Strategic Management Journal, 1986)
Abstract Only by developing management systems based on appropriate standards can a business successfully learn how to improve the technology of work. As a result, a new economics of work is created where the evolution of large organizations makes economic sense. But economies of scale no longer require rigid mass production of a limited product line. Flexibility can be introduced to produce product diversity without losing the efficiencies of standardization. Thus manufacturing can operate more flexibly like a service by learning to apply industrial robots and other smart machines. Service businesses can also learn how to manage more systematically by designing standard menus of operations.